Oil and Conflict in the Niger Delta: A Reflection on the Politics of State Response to Armed Militancy in Nigeria - Bassey, Celestine Oyom (Mediterranean Journal of Social Sciences, 2012)
The Niger Delta is currently in the vortex of protracted social conflict, as crisis of regime legitimacy, â€œpolitical ostracismand social marginalizationâ€ fuel armed rebellion with incalculable consequences for the stability of the Nigerian state. The rootcause of this crisis has been the subject of extensive debate in the literature (Otite, 1990; Bassey, etal, 2002). The currentdimension of the crisis is arguably the systemic resultant of the multiple disorders (intense â€œbureaucratic politicsâ€) in the policyprocess under the Obasanjo administration and that of his successor, Yarâ€™ Adua â€“Jonathan, and the equal determination ofmilitant youth movements (MEND, NDV, etc.) to assert their presence in the region. This melodrama is currently played out inthe official circle of Nigeriaâ€™s Federal Government with the unmistakable paradigm shift of policy discourse from accommodationand commitment to transformative action to the language of criminality, gangsterism, terrorism and force. While thesecontending tendencies characterized bureaucratic debate in the Nigerian policy circles (with the military establishment pushingfor a â€œfinal solutionâ€ in line with the decisive action against Biafran secession), the military onslaught on the militant camps in theNiger Delta in May 2009 marked a watershed in the praxis of state response through force. The implication is unmistakable: withless sympathy for the struggle against â€œdomestic colonialism in the region, the dominant mindset of the Yarâ€™ Adua- Jonathanadministration (the â€œgroup think factorâ€) is committed to the Colombian or Zaireen style solution. How this dialectics of force andresistance is played out will determine the future of Nigeria in the next decade: failed, collapsed or problem state?